HSF1 at the crossroads of chemoresistance: from current insights to future horizons in cell death mechanisms - Ghai, Shruti; Shrestha, Rejina; Su, Kuo-Hui (Frontiers in Cell and Developmental Biology, 2025)
Heat Shock Factor 1 (HSF1) is a major transcriptional factor regulating the heat shock response and has become a potential target for overcoming cancer chemoresistance. This review comprehensively examines HSF1’s role in chemoresistance and its potential as a therapeutic target in cancer. We explore the complex, intricate mechanism that regulates the activation of HSF1, HSF1’s function in promoting resistance to chemotherapy, and the strategies used to manipulate HSF1 for therapeutic benefit. In addition, we discuss emerging research implicating HSF1’s roles in autophagy, apoptosis, DNA damage repair, drug efflux, and thus chemoresistance. This article highlights the significance of HSF1 in cancer chemoresistance and its potential as a target for enhancing cancer treatment efficacy.